2013
DOI: 10.5551/jat.16089
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between the Level of High-Sensitivity C-Reactive Protein and Cardiovascular Risk Factors in Korean Adults with Cardiovascular Disease or Diabetes Mellitus: The CALLISTO Study

Abstract: Aim:We assessed the relationship between the level of high-sensitivity C-reactive protein (hsCRP) and cardiovascular risk factors in Korean adults. Methods: We reviewed 1,561 patients with cardiovascular disease or diabetes mellitus with hsCRP levels measured within the past year. Four cardiovascular risk groups were determined: low (<10%, 0-1 risk), moderate (<10%, >2 risk), high (10-20%) and very high (>20%) risk, according to the number of risk factors and the Framingham/NCEP ATP Ⅲ risk score. The correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
4
18
1
Order By: Relevance
“…These results converge with the previous report of Seo et al [90] which showed that levels of hs-CRP are significantly correlated with the level of glycosylated hemoglobin, LDL/HDL ratio, LDL/total cholesterol (TC) ratio, and TC/TG ratio in diabetic patients or patients with CVD. Furthermore, Bahceci et al [91] observed positive correlation between serum hs-CRP and glycated hemoglobin in T2DM with or without CHD.…”
Section: Fig 2: Correlation Between Different Metabolic Parameters Asupporting
confidence: 92%
“…These results converge with the previous report of Seo et al [90] which showed that levels of hs-CRP are significantly correlated with the level of glycosylated hemoglobin, LDL/HDL ratio, LDL/total cholesterol (TC) ratio, and TC/TG ratio in diabetic patients or patients with CVD. Furthermore, Bahceci et al [91] observed positive correlation between serum hs-CRP and glycated hemoglobin in T2DM with or without CHD.…”
Section: Fig 2: Correlation Between Different Metabolic Parameters Asupporting
confidence: 92%
“…High-sensitivity C-reactive protein (hs-CRP) is produced by hepatocytes and is involved in inflammation. Clinical studies have demonstrated that hs-CRP levels can be used as predictors of cardiovascular disease (5). Matrix metalloproteinase 9 (MMP-9, also known as gelatinase B), which has numerous substrates, is involved in a wide range of physiological functions, including regulation of protease and cytokine activity (6).…”
Section: Introductionmentioning
confidence: 99%
“…Among patients without diabetes mellitus who were not receiving statin therapy, approximately 30% had CRP levels ≥3 mg/L, and approximately 50% had CRP levels ≥2 mg/L, including those at intermediate levels of traditionally estimated cardiovascular risk. Also, Seo SM, et al (53) found that the levels of hs-CRP were significantly increased from the low to the very high risk group (0.15, 0.23, 0.27 and 0.47, respectively) and were significantly correlated with age, BMI, the levels of HDL-ch, LDL-ch/HDL-ch ratio, the LDL-ch/total cholesterol (TC) ratio, the HDL-ch/TC ratio, the HDL-C/triglyceride (TG) ratio and the TC/TG ratio. In a multivariate regression analysis, age, the HDL-C level, the LDL-C/TC ratio and BMI were found to be independently correlated with the hs-CRP level.…”
Section: Discussionmentioning
confidence: 98%